Systematic Review of En Bloc Resection in the Management of Ewing's Sarcoma of the Mobile Spine with Respect to Local Control and Disease-Free Survival. Issue 27 (July 2015) - Sewell, Mathew David; Tan, Kimberly-Anne; Quraishi, Nasir A.; Preda, Corina; Varga, Peter P.; Williams, Richard; Jereb., Berta
<x xml:space="preserve">Abstract</x> Abstract There is no consensus on the optimal method of local control in Ewing's sarcoma (ES) of the mobile spine. Recent reports have suggested that en bloc resection may improve local control and survival. The authors therefore performed a systematic review to answer the following questions: (1) What is the outcome of en bloc resection for ES of the mobile spine with respect to local control and disease-free survival (DFS)? (2) How should residual ES of the mobile spine be treated? Inclusion criteria were articles published between the years 1960 and 2014 in English that contained more than five patients. This yielded 204 articles, from which 4 were selected for detailed analysis. The literature was graded for quality, summarized, and presented to a group of spinal oncology experts with consensus recommendations made. All 4 studies were retrospective case series graded as very low quality evidence. Local control strategies included radiotherapy (RT) alone, surgery and RT, or surgery alone. There was no standardized outcome reported across studies with respect to the type of surgical procedure, margins, and outcomes of interest such as local recurrence (LR) and DFS. When the en bloc procedures were pooled together, 2 of the 21 patients with available LR data developed LR (9.5%), and 5 of the 7 patients with available DFS data were disease free at a mean of 76 months. The remaining 2 died at 10 and 29 months, respectively. No studies were identified detailing the treatment of residual ES of the mobile spine. There is no consensus on the optimal method of local control for spinal ES or the treatment of residual disease. A weak recommendation supports that when the en bloc resection is technically possible, in combination with RT, this appears to provide superior local control than RT alone, or incomplete excision and RT. The effect on survival is indeterminate.